Microbial Protein Production and Nitrogen Balance of Local Steer Fed Ammoniated Rice Straws Added - Hindratiningrum, H; Bata, M; Suparwi, Suparwi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
The objective of the experiment was to investigate the kind of energy source feedstuffs on nutrient balance and microbial protein synthesis in local male beef cattle fed with ammoniated rice straws Twenty steers Peranakan Ongole (PO) with average age 1-2 years old were used. They were divided 5 groups based on initial body weight as block. Therefore, Completely Randomised Block Design (CBRD) was used for this experiment. Data were analysed by analysis variance and continued honestly significant different (HSD) to test the differences between means. The result showed that the range MCP and eficiency MCP were 154,61 g/d until 226,54 g/d and 54,08 gMCP/kg DOMR until 62,64 gMCP/kg DOMR. The range of nitrogen balance were 72,28 gram until 111,67 gram. MCP and efficiency MCP were not affected (P>0,05) by the treatments but balance of nitrogen was affected (P<0,05). Diet containing fresh cassava waste as energy source (R2) was lower (P<0,05) than R1 and R4 while between R1,R3 and R4 was similar. This results indicate that feed source of energy (rice brand, wet cassava waste, dry cassava waste and corn) can be used in steers with rice straw ensilage as forage. (Animal Production 11(2): 116-121 (2009) Key Words : Microbial protein production, nitrogen balance, rice straw, ensilage